Technology Transfer in Global Value Chains - Thomas Sampson (Center for Economic Studies and ifo Institute (CESifo), 2022)
Firm-to-firm relationships in global value chains create opportunities for North-South technology diffusion. This paper studies technology transfer in value chains when contracts are incomplete and input production technologies are imperfectly excludable. The paper introduces a new taxonomy of value chains based on whether or not the headquarters firm benefits from imitation of its supplier's technology. In inclusive value chains, where imitation is beneficial, the headquarters firm promotes technology diffusion. By contrast, in exclusive value chains headquarters seeks to limit supplier imitation. The paper analyzes how this distinction affects the returns to offshoring, the welfare effects of technical change and the social efficiency of knowledge sharing. Weaker intellectual property rights over input production technologies raise welfare when value chains are inclusive, but have the opposite effect under exclusive value chains.
Keywords: D23; F10; F23; O34; 330; technology transfer; global value chains; incomplete contracts; intellectual property rights; imitation